2023
DOI: 10.1186/s13059-023-02949-2
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling group heteroscedasticity in single-cell RNA-seq pseudo-bulk data

Abstract: Group heteroscedasticity is commonly observed in pseudo-bulk single-cell RNA-seq datasets and its presence can hamper the detection of differentially expressed genes. Since most bulk RNA-seq methods assume equal group variances, we introduce two new approaches that account for heteroscedastic groups, namely voomByGroup and voomWithQualityWeights using a blocked design (voomQWB). Compared to current gold-standard methods that do not account for group heteroscedasticity, we show results from simulations and vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…BCV, a key indicator of biological variability in gene expression among biological replicates, is widely used for estimating gene expression variance in RNA-Seq data 45 . Following previous studies 72 , here we demonstrate group heteroscedasticity by comparing the variability in group-specific BCV values and visualize this effect in the form of distinctive positions and shapes of group-specific mean-variance trend curves across these twelve diverse datasets (Fig. S1).…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…BCV, a key indicator of biological variability in gene expression among biological replicates, is widely used for estimating gene expression variance in RNA-Seq data 45 . Following previous studies 72 , here we demonstrate group heteroscedasticity by comparing the variability in group-specific BCV values and visualize this effect in the form of distinctive positions and shapes of group-specific mean-variance trend curves across these twelve diverse datasets (Fig. S1).…”
Section: Resultsmentioning
confidence: 64%
“…1). Our approach mirrors that of a previous study 72 which identified group heteroscedasticity through higher biological coefficient of variation (BCV) values in one group compared to another. BCV, a key indicator of biological variability in gene expression among biological replicates, is widely used for estimating gene expression variance in RNA-Seq data 45 .…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations